Review: Neuropathology and behavioural features of transgenic murine models of Alzheimer's disease. (9th November 2017) - Ameen‐Ali, K. E.; Wharton, S. B.; Simpson, J. E.; Heath, P. R.; Sharp, P.; Berwick, J.
Abstract : Our understanding of the underlying biology of Alzheimer's disease (AD) has been steadily progressing; however, this is yet to translate into a successful treatment in humans. The use of transgenic mouse models has helped to develop our understanding of AD, not only in terms of disease pathology, but also with the associated cognitive impairments typical of AD. Plaques and neurofibrillary tangles are often among the last pathological changes in AD mouse models, after neuronal loss and gliosis. There is a general consensus that successful treatments need to be applied before the onset of these pathologies and associated cognitive symptoms. This review discusses the different types of AD mouse models in terms of the temporal progression of the disease, how well they replicate the pathological changes seen in human AD and their cognitive defects. We provide a critical assessment of the behavioural tests used with AD mice to assess cognitive changes and decline, and discuss how successfully they correlate with cognitive impairments in humans with AD. This information is an important tool for AD researchers when deciding on appropriate mouse models, and when selecting measures to assess behavioural and cognitive change. Abstract : Reviewing mouse models of Alzheimer's disease the authors focus on how the models reflect physiological, neuropathological and cognitive changes of the human disease. The review highlights the points for consideration in selecting mouse models for study and interpreting findings in such studies.